Mathematical and Simulation Model Development of Switched Reluctance Motor - S. V. Aleksandrovsky; Y. N. Petrenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The switched reluctance motor (SRM) represents a great interest while being applied in various fields as an alternative to asynchronous motors with a short-circuit rotor. A SRM disadvantage is a nonlinearity of its characteristics. Due to this reason it is desirable to execute investigations using a developed simulation model. The simulation results (electromagnetic torque and current) are in good agreement with those values studied in the literature.